Integration of Sports and Medicine in China: Exploring Talent Training Strategies for Physical Education Majors - Xu Zhang, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The integration of sports and medicine and its link with the public health has evolved as paradigm shift in both the medicine and physical education. Youth is central to this and to prepare them for a healthy; lifestyle colleges and universities should not forego offering physical education as a major, as well as requiring individuals from all walks of life to implement this concept, as the integration of sports and medicine is not only an emerging paradigm but also an innovative concept for modern health care. To bridge the between the healthcare needs of the country's population and the services that are currently available Healthy China 2030 plan coined the integration of sports and medicine (ISM), and subsequently policymakers the Chinese government has issued a number of calls and implemented a number of measures to promote the integration of locally tailored sports and medical institutions. To examines the talent training strategy of college and university physical education majors from the angle of sports and medicine integration, the study has employed the literature review methodology coupled with deductive reasoning. The prime objective of the study is to contribute to the evolution of university physical education programs. In an effort to achieve the objective of the study the study investigates the talent training strategy of college and university majoring in physical education and its integrating sports and medicine. Beijing, Shanghai, and Tianjin, the three Chinese cities are used as case studies to explain the ISM and its implementations in China. The study will be helpful for policymakers, researchers, and sports centers in understanding the link between physical education and ISM.